PLCs I/O Communication - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The PLCs: I/O Communication training program, or unit, is designed to familiarize trainees with the various ways in which real-world devices can be connected to the input and output systems of a programmable logic controller. After completing this program, the trainees should be able to identify various types of I/O modules and field devices, and explain how direct I/O connections are made. They should also be able to identify some common device networks and identify some devices, other than PLC devices, that you might find on a typical device network.
Keywords: Computer input-output equipment; Programmable controllers